2000
DOI: 10.1080/10412905.2000.9699565
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Constituents ofNepeta denudataBenth. andN. cephalotesBoiss. from Iran

Abstract: School OJ' I'hurmu cy, Shuheed Uehesht i I /I? iiJetXitY of Medicul Scieiices PO Box 141 55 -67 5.3 Tehran, Iran h a m Monfared Ileparl meiat ($ C'hem ishy, Shaheed Ueheshr i 1 ln ii wsi!y, Lvemi, 7 kh rU 11, Iran Kobra Nadji School of I'hurmacy, Tehran Unii~enity OJ'Medicul Sciences, 7?hran, Iran AbstractThe composition o f the essential oils of Nepta &izuc(cctuBenth. and N. cephalores noiss., which arc endemic t o Iran, was investigated by means o f GC, GC/MS and 'H-NMR spectra of the main compounds, 1,8-cin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 7 publications
1
23
0
Order By: Relevance
“…The amount of 4aα,7α,7aα-nepetalactone (92.6%) was almost the same as N. caesarea (91.2%) 12 and N. teydea (89.54%), 11 and was higher than other species of Nepeta, such as N. racemosa (64.9%), 7 N. cadmea (44.5%), 13 and N. cephalotes (35.1%), 9 N. binaludensis (25.2%). 10 A trace of 4aα,7α,7aβ-nepetalactone and 4aβ,7α,7aα-nepetalactone were detected in this plant.…”
Section: Resultsmentioning
confidence: 83%
“…The amount of 4aα,7α,7aα-nepetalactone (92.6%) was almost the same as N. caesarea (91.2%) 12 and N. teydea (89.54%), 11 and was higher than other species of Nepeta, such as N. racemosa (64.9%), 7 N. cadmea (44.5%), 13 and N. cephalotes (35.1%), 9 N. binaludensis (25.2%). 10 A trace of 4aα,7α,7aβ-nepetalactone and 4aβ,7α,7aα-nepetalactone were detected in this plant.…”
Section: Resultsmentioning
confidence: 83%
“…Notable amounts (1-2 g/100 g) were determined for 1,3,5-trimethylbenzene, p-cymene, camphor, pinocarvone and borneol. Apart from a report in an Iranian journal, [14] there is no evidence of analytical studies on A. oliveriana. This bibliographic reference confirms the presence of eucalyptol and pinocarvone as main constituents but, surprisingly, no α-thujone was detected in the present study, despite of the findings presented in the Iranian report.…”
Section: Resultsmentioning
confidence: 89%
“…[12] Finally, Ramezani et al investigated the antimicrobial activity of A. diffusa and A. oliveriana. [13] Available data on the volatile composition of the oil of A. oliveriana are very scarce; an article by Rustaiyan et al [14] describes its chemical composition as characterized mainly by α-thujone, while two other studies reported the presence of flavonoids and sesquiterpene lactones, namely melampolides, in the non-volatile fraction. [15,16] The aim of this paper is to bring up to date the information on the chemical composition of these particular species of Artemisia plants coming from Iran, by means of accurate GC-MS and GC-FID analyses.…”
Section: Introductionmentioning
confidence: 98%
“…[13][14][15][16][17][18][19] trans-Carveol, which was found as a second major component of the oil, has been reported in the oils of some similar or other Nepeta spp. [14][15][16][17][20][21][22] The third major constituent of the oil, β-cubebene, was previously found in Nepeta spp. as well as in oil from an Iranian Hymenocrater taxon.…”
Section: Resultsmentioning
confidence: 98%